2022
DOI: 10.1021/acs.iecr.1c04941
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Flow Rate Distribution in a Crude Oil Preheat Train Considering Fouling Deposition in Shell and Tube Sides

Abstract: The deposition of an undesired material on the heat transfer surfaces is a recurrent problem that affects the overall performance of heat exchanger networks (HENs). A wide variety of empirical and semiempirical models are available for predicting the fouling behavior. In this work, there are considered different predominant fouling mechanisms at each side of the shell and tube heat exchangers used to preheat crude oil from a refinery. Adopting the mass flow rates at the parallel branches of the HEN as optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It exhibits nonconvex and nonlinear characteristics, thereby posing challenges in obtaining the entire set of Pareto optimal solutions through conventional optimization algorithms. Numerous researchers have proposed various algorithms, such as sequential quadratic programming, simulated annealing, and genetic algorithm. Numerous studies have demonstrated that the utilization of NSGA-III yields remarkable results when addressing complex many-objective optimization issues. NSGA-III is a genetic algorithm employed for solving issues of multi-objective optimization.…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits nonconvex and nonlinear characteristics, thereby posing challenges in obtaining the entire set of Pareto optimal solutions through conventional optimization algorithms. Numerous researchers have proposed various algorithms, such as sequential quadratic programming, simulated annealing, and genetic algorithm. Numerous studies have demonstrated that the utilization of NSGA-III yields remarkable results when addressing complex many-objective optimization issues. NSGA-III is a genetic algorithm employed for solving issues of multi-objective optimization.…”
Section: Introductionmentioning
confidence: 99%